Proceedings of the National Conference on Small-Scale Industries and the Development of Nigeria, Feb. 22-25, 1987 - Igwe, B. U. N.; Akinbinu, A. F.; Banwo, P. A.; Nigerian Institute of Social and Economic Research (Ibandan : Nigerian Institute of Social & Economic Research, Business & Projects Consultancy Dept., 1987)
This proceedings are compilation of paper presented at the Nigerian institute of social and economic research (NISER) Ibadan in the year 1987. Reviews from the conference was to create an awareness of the critical issues involved in the development of small-scale industries in Nigeria.
Cover title.
Conference held at the University of Ibadan.
"March 1987."
Includes bibliographical references.
asm; 12/04/19
Loans
Keywords: Small business; Small business